Cardiac biomarkers and left ventricular systolic function in former very preterm infants and term controls at preschool age - Höck, Michaela; Posod, Anna; Odri Komazec, Irena; Griesmaier, Elke; Ralser, Elisabeth; Pupp-Peglow, Ulrike; Kiechl-Kohlendorfer, Ursula (Frontiers in Pediatrics, 2024)
Introduction Due to improvements in perinatal care, survival rates of preterm infants have improved during the last decades. However, these infants remain at risk of developing cardiovascular sequelae later in life. This study aimed to investigate the cardiac biomarkers and left ventricular systolic function in former preterm infants in comparison with term controls at preschool age. Methods The study included children aged 5–7 years old born below 32 weeks of gestational age. The control group consisted of same-age children born at term. Basic data of study participants were collected using questionnaires and follow-up databases. During the study visit, we recorded anthropometric data and blood pressure readings, determined high-sensitive cardiac troponin T (hs-cTnT) and N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) concentrations, and calculated fractional shortening (FS) and left ventricular mass (LVM). Results Term-born (n = 25; median gestational age, 40.1 weeks) compared with preterm-born infants (n = 80; median gestational age 29.6 weeks) showed no significant differences in the median concentration of hs-cTnT [median, 3.5 (IQR 3.5; 3.5) vs. 3.5 (3.5; 3.5) ng/L, p = 0.328] and the median concentration of NT-pro-BNP [median, 91.0 (IQR 40.8; 150.3) vs. 87.5 (50.1; 189.5) ng/L, p = 0.087]. FS and LVM/LVMI were not significantly different between the two groups. Conclusion At preschool age, we observed no significant differences in cardiac biomarkers and left ventricular systolic function in preterm infants. Further studies are warranted to explore the potential of cardiac biomarkers as a prognostic tool for subclinical cardiac alterations after preterm birth.